2021
DOI: 10.1038/s42003-021-01724-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and genomic comparisons of hybrid uninucleate and nonhybrid Rhizoctonia fungi

Abstract: The basidiomycetous fungal genus, Rhizoctonia, can cause severe damage to many plants and is composed of multinucleate, binucleate, and uninucleate species differing in pathogenicity. Here we generated chromosome-scale genome assemblies of the three nuclear types of Rhizoctonia isolates. The genomic comparisons revealed that the uninucleate JN strain likely arose by somatic hybridization of two binucleate isolates, and maintained a diploid nucleus. Homeolog gene pairs in the JN genome have experienced both dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 110 publications
0
21
0
Order By: Relevance
“…Lesion lengths caused by the challenge of R. solani XN strain were markedly reduced upon knockout of OsSAH3 (sah3KO), and both OsSAH2 and OsSAH3 (sah2&sah3KO) plants, whereas the lesion lengths were increased in the CDU::SAH3-and 35S::SAH3-GFP-overexpressing plants (Figure 4d). Furthermore, the plants harboring OsSAH3-overexpressing constructs were infected with a weak virulent uninucleate Rhizoctonia JN isolate [29]. OsSAH3-overexpressing plants were more susceptible to JN isolate than the ZH17 control plants (Figure S9).…”
Section: Knockout Ossah2-3 Genes Enhance Resistance Against Hemibiotr...mentioning
confidence: 99%
“…Lesion lengths caused by the challenge of R. solani XN strain were markedly reduced upon knockout of OsSAH3 (sah3KO), and both OsSAH2 and OsSAH3 (sah2&sah3KO) plants, whereas the lesion lengths were increased in the CDU::SAH3-and 35S::SAH3-GFP-overexpressing plants (Figure 4d). Furthermore, the plants harboring OsSAH3-overexpressing constructs were infected with a weak virulent uninucleate Rhizoctonia JN isolate [29]. OsSAH3-overexpressing plants were more susceptible to JN isolate than the ZH17 control plants (Figure S9).…”
Section: Knockout Ossah2-3 Genes Enhance Resistance Against Hemibiotr...mentioning
confidence: 99%
“…[51,52], with genome-based quantitative comparisons (e.g. Jaccard index of genomic distance (the fraction of shared k-mers), identification of syntenic blocks, and Average Nucleotide Identity (ANI) [15,18]) being more heavily utilized and often for delineating lower taxonomic level (e.g. species) boundaries.…”
Section: Phylogenomic Analysis the Phylogenomic Analysis Includes 20 ...mentioning
confidence: 99%
“…Comparative genomics approaches (e.g. calculation of shared Kmer (Kmer overlap) [15,16], average nucleotide identity (ANI) [17], identification of genomic syntenic blocks [18]) have been increasingly utilized in taxonomic studies, aided by the development of lower cost high . CC-BY-ND 4.0 International license available under a was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%
“…It also has an explicit evolutionary model for data and better accounting for branch length ( Mishler, 2006 ). For example, Li et al (2021) and Xu et al (2020) used the ML algorithm in RAxML to construct a genome-based phylogenetic tree. In this study, based on the ML/NJ phylogenetic analysis of S. edulis and 31 other species of fungus, it was shown that the Sarcomyxa genus is a distinct group.…”
Section: Discussionmentioning
confidence: 99%